In utero Undernutrition Programs Skeletal and Cardiac Muscle Metabolism - Beauchamp, Brittany; Harper, Mary-Ellen (Frontiers in Physiology, 2016)
In utero undernutrition is associated with increased risk for insulin resistance, obesity, and cardiovascular disease during adult life. A common phenotype associated with low birth weight is reduced skeletal muscle mass. Given the central role of skeletal muscle in whole body metabolism, alterations in its mass as well as its metabolic characteristics may contribute to disease risk. This review highlights the metabolic alterations in cardiac and skeletal muscle associated with in utero undernutrition and low birth weight. These tissues have high metabolic demands and are known to be sites of major metabolic dysfunction in obesity, type 2 diabetes, and cardiovascular disease. Recent research demonstrates that mitochondrial energetics are decreased in skeletal and cardiac muscles of adult offspring from undernourished mothers. These effects apparently lead to the development of a thrifty phenotype, which may represent overall a compensatory mechanism programmed in utero to handle times of limited nutrient availability. However, in an environment characterized by food abundance, the effects are maladaptive and increase adulthood risks of metabolic disease.